2006
DOI: 10.1111/j.1525-1438.2006.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body positron emission tomography with F-18 fluorodeoxyglucose for the detection of recurrence in uterine sarcomas

Abstract: We evaluated the usefulness of whole-body positron emission tomography (PET) using F-18 fluorodeoxyglucose (FDG-PET) for the detection of recurrence in follow-up patients after primary treatment of uterine sarcoma. Eight patients with pathologically proven uterine sarcoma underwent FDG-PET, computed tomography (CT), and ultrasonography (US). Final diagnoses of recurrence were established in five cases (three carcinosarcomas and two leiomyosarcomas). PET revealed recurrent sites in the intraperitoneum, liver, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Though this modality appears to offer the possibility of earlier detection of metastases, there was no reported improvement in patient outcome data in this study [31]. Another study by Murakami et al suggests that in patients with recurrent uterine carcinosarcomas, FDG-PET may increase prolonged survival, especially in those with small tumours treated with combination therapy [50]. 18 F-PDG PET scans seem to have limited value in posttherapy surveillance or restaging after failure with recurrence [31].…”
Section: Radiologymentioning
confidence: 76%
“…Though this modality appears to offer the possibility of earlier detection of metastases, there was no reported improvement in patient outcome data in this study [31]. Another study by Murakami et al suggests that in patients with recurrent uterine carcinosarcomas, FDG-PET may increase prolonged survival, especially in those with small tumours treated with combination therapy [50]. 18 F-PDG PET scans seem to have limited value in posttherapy surveillance or restaging after failure with recurrence [31].…”
Section: Radiologymentioning
confidence: 76%
“…In fact, in this study, PET scan, show a very good accuracy (94,4%) in women with suspected recurrence and a good sensitivity (87,5%) in asymptomatic women and contribute to change the treatment in 1/3 of the population. The results of the few small reports are encouraging in this way, but not completely in agreement [72,76,77].…”
Section: Uterine Sarcomasmentioning
confidence: 75%
“…During the follow-up about one half of Stage I cases develop a recurrence [72]. In the management of sarcomas (soft tissues and bone sarcoma), the current literature evidences discordant data on the accuracy and the usefulness of 18 F-FDG-PET scan due to the small number and to the heterogeneity of the included cases; however, PET seems to be capable of differentiating between low and high grade sarcomas, and in the evaluation of residual disease after therapy [73].…”
Section: Uterine Sarcomasmentioning
confidence: 99%
“…[112][113][114][115] FDG-PET/CT has been reported to have a higher detection rate compared with CT alone for the detection of extrapelvic recurrence. The sensitivity of PET/CT was 100% compared with 85.7% for CT. 116,117 Park et al 118 evaluated 36 patients and found FDG-PET/CT to have a sensitivity, specificity, accuracy, PPV, and NPV of 92.9%, 100%, 94.4%, 100%, and 80%, respectively, in symptomatic patients and 87.5%, 95.5%, 93.3%, 87.5%, and 95.5%, respectively, in asymptomatic patients. They also found that FDG-PET/CT altered the treatment plan in 33.3% of the patients with suspected recurrence.…”
Section: Uterine Sarcomamentioning
confidence: 97%